Monacolin K as a Natural Alternative for Synthetic Statins - Julia Kozakiewicz; Aleksandra Okońska; Michał Ziemba; Kamil Kościelecki; Agnieszka Kalisz; Magdalena Krakowiak; Aleksandra Kaczmarek (Quality in Sport)
Introduction: This review paper aims to verify the safety of monacolin K, examine the effect on blood cholesterol levels, discuss the contribution to the reduction of cardiovascular risk and indicate examples of pleiotropic effects of this substance.